Evaluation of Development of Achievement of Judo Athletes in Bantul Regency Yogyakarta Special Region Province - Budi Laksono; Ardhika Falaahudin (Journal Physical Health Recreation (JPHR), 2022)
This study aims to determine whether the judo district of Bantul has implemented the training program well or not and to find out the shortcomings of athletes during their time as judo athletes in Bantul so that they can be improved and can achieve many achievements. This study uses a quantitative descriptive design with a survey method. The population in this study were judo athletes in Bantul district with 23 male and female athletes. In this study using data analysis techniques using questionnaires filled in by respondents, namely 23 judo athletes in Bantul district and pie charts as a measuring tool for research results that can be described or explained in detail to obtain conclusions from the study. This questionnaire has been validated using SPSS software for windows and also Microsoft excel so that the questions and statements that are distributed to be filled in are truly valid. The results of this study are that there are some athletes who still have deficiencies or incompatibility with the training program provided by Judo Bantul and there are deficiencies in Judo Bantul related to the training program given to athletes.